ESTIMATION OF THE BEST LINEAR UNBISED PREDICTION (BLUP) OF KURDI RAMS FOR AVERAGE DAILY MILK YIELD DEPENDING ON THEIR PROGENY - & et al., Raoof (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted at Erbil plain, Kurdistan region- Iraq during the period from July/2015 to June/2016. The study included 189 Kurdi ewes and 21 rams. The study aimed to estimate the Best Linear Unbiased Prediction (BLUP) values of sires for daily milk yield and to study the effect of the non-genetic factors (Age of dam, sex and type of birth, estrous sequences cycle and ewes weights at lambing) and to estimate the heritability and repeatability for average daily milk yield. The overall mean of daily milk production was 384.56g. The weight and age of dam showed a significant effect (p